Institution Based Tumor Registry, Benazir Bhutto Hospital: A Four Year Data Based Analysis - Behzad Masood, Behzad Masood; Afzaal Aleem Khan, Afzaal Aleem Khan; Muhammad Usman, Muhammad Usman; Ammara Ijaz, Ammara Ijaz; Furqan Ali Taj, Furqan Ali Taj; Faisal Javed, Faisal Javed; Muhammad Soban Saeed, Muhammad Soban Saeed (Students’ Supplement of Journal of Rawalpindi Medical College, 2022)
Background: To retrieve all diagnosed cancer cases during the past four years (2014-2017) in Benazir Bhutto Hospital, Rawalpindi, and categorize them by organ sites affected/ topographically, to determine cancers with the highest prevalence in our part of the world. Materials & Methods: A hospital registry-based retrospective study was undertaken in the Department of Pathology of Benazir Bhutto Hospital, Rawalpindi. All diagnosed cases of cancer for the past four years that had been histologically confirmed, were retrieved. The cancer cases thus obtained were then classified topographically, according to the International classification of diseases for oncology. The data obtained was then analyzed using SPSS v.23 into percentage frequencies and ranked with respect to gender, and presented using tables and figures. Results: Urinary Bladder, Breast, Prostate, Skin, Kidney, Colorectum, Cervix, Esophagus, Uterus and Vulva were in descending order the 10 leading sites overall. Carcinoma of the Urinary Bladder emerged as the leading cancer in males, comprising 30.7% of male cases, followed by Prostate (24.7%), Skin (16.3%), Colorectum (5.6%), Kidney (5.6%) and Stomach (2.4%). The most common site of cancer in females was Breast (36.2%), followed in decreasing order by Cervix (8.6%), Kidney (7.6%), Urinary Bladder (7.1%), Skin (7.1%), and Esophagus (6.2%). Conclusion: In conclusion, the cancer pattern revealed by this study provides valuable leads to cancer epidemiology in the region. The two most common cancer sites in males were urinary bladder (30.7%) and prostate (24.7%), whereas in females they were breast (36.2%) and cervix (8.6%). Key Words: Tumor registry; Cancer pattern